Monitoring System for Mushroom Cultivation in Indoor Farming using ESP32 Arduino - Abdul Malik, Muhammad Fikri; Vajravelu, Ashok; R.P. Karthik, (Evolution in Electrical and Electronic Engineering, 2022)
This Monitoring System is to observe mushroom cultivation in indoor farming using ESP32 Arduino. Also can monitor mushroom cultivation on the shed that apply in the hardware been developed with MQ-135, DHT11 and soil moisture sensor to notify the gases and temperature on the environment indoor, also the condition of the soil for the mushroom. The LED and buzzer are applied to the shed as indicators to the user can compare the gases, temperature and soil moisture conditions for mushroom cultivation. Hence, the hardware was installed with DC Fan and pump water to control the condition of the hardware if the above the range that has been set on the ESP32 using Arduino IDE. The user can notify the user using Blynk application that has been linked to ESP32 Arduino. It can ease the farmer to monitor mushroom cultivation indoors. Reading also been taken by 2 parameters for 70 days for the hardware and analyze with 2 mushroom bags within 2 conditions indoor and indoor with a monitoring system for 5 days. Mushrooms grow quicker indoors with a monitoring system than indoors without a monitoring system. This is due to the fact that the mushrooms are exposed more to the environment and controlled by parameters been developed.